Unlocking the power of exercise / Dr. Farah Adilla Ab. Rahman and Ms. Jeniwaty Mohd Jody - Ab. Rahman, Farah Adilla; Mohd Jody, Jeniwaty (Universiti Teknologi MARA, Negeri Sembilan, 2024)
“Move for health: Reducing the risk of noncommunicable diseases through physical activity!” Physical inactivity stands as a modifiable risk factor akin to dyslipidemia and hypertension, contributing significantly to the onset of various chronic diseases, including cancer and cardiovascular ailments. However, exercise emerges as a potent tool in mitigating these risks, offering substantial health benefits that extend to both primary and secondary prevention of such diseases, with a notable reduction in cardiovascular ailments and premature mortality. Past study asserts that the physiological mechanisms facilitating these benefits operate at both cellular and multisystem levels [1]. Indeed, there is irrefutable evidence attesting to the efficacy of regular physical activity in averting a spectrum of chronic diseases and premature death, as highlighted by [2].